Canada-Wide Effect of Regulatory Warnings on Antidepressant Prescribing and Suicide Rates in Boys and Girls. (November 2013) - Rhodes, Anne E; Skinner, Robin; McFaull, Steven; Katz, Laurence Y
Objective: To examine the impact of the Health Canada regulatory warnings regarding antidepressant (AD) prescribing on suicide rates in boys and girls under the age of 18 and aged 18 to 19 years in Canada between 2004 and 2009. We hypothesized that an increase in suicide rates would be specific to girls, reflecting higher AD prescribing rates in girls than boys. Method: We graphed and tested the difference between Canada-wide suicide rates before and after the regulatory warning periods (either from 1995 to 2006 or from 1995 to 2009) in boys and girls under the age of 18 or aged 18 to 19 years. For comparison with prior studies, we estimated rate ratios and 95% confidence intervals using either Poisson regression or negative binomial regression. Results: There was no statistically significant increase in suicide rates in girls under the age of 18, or aged 18 to 19 years in response to the AD regulatory warnings. In boys under the age of 18 or aged 18 to 19 years, suicide rates declined after 2003. Conclusions: We did not find increased rates of suicide after the AD regulatory warnings in boys or girls under the age of 18 or aged 18 to 19 years in Canada-wide rates. However, this does not rule out the possibility that such an effect occurred in some jurisdictions in girls and (or) the regulatory warnings prevented the trend toward declining suicide rates. Factors influencing the downward trend in boys merit further attention.